Costs of housing crises: International evidence - Christian Aßmann; Jens Boysen-Hogrefe; Nils Jannsen (Kiel Institute for the World Economy (IfW), 2009)
This analysis provides evidence for the costs housing crises induce in terms of GDP growth and under what circumstances these crises are particularly costly. Housing crises are often followed by recessions that are longer and deeper than other recessions. According to empirical estimates, a housing crisis reduces the GDP growth rate in the following year on average by 2.5 percentage points and has a further negative impact in the second year. One important channel transmitting the additional effect of housing crises works through the depression of the construction sector, while wealth effects play a minor role.
More recent version: http://hdl.handle.net/10419/130548
Keywords: E21; E32; C23; 330; Housing crisis; Panel Data; Immobilienmarkt; Branchenkrise; Konjunktur; Soziale Kosten; Industriestaaten